Novel compound, organic cation transporter 3 detection agent and organic cation transporter 3 activity inhibitor, WO2015002150 A1: a patent evaluation. (2nd August 2016) - Hu, Tao; Wang, Li; Pan, Xiaolei; Qi, Hualin
ABSTRACT: Increasing pharmacological studies have demonstrated that organic cation transporter 3 (OCT3) plays an important role in controlling the extracellular concentrations of released monoamine neurotransmitter, suggesting that OCT3 might be a promising target in the treatment of depression. As a consequence, compounds showing inhibitory effects on the function of OCT3 have the potential for depression treatment. The current patent WO2015002150 A1 described the synthesis of 59 novel guanidine derivatives. All investigated compounds exhibited significant inhibitory effects (41.9–88.2%) on human OCT3 activity at 30 µM, using human OCT3-transfected human embryonic kidney 293 cell. Concentration-response curves (IC50 values) were determined for seven compounds with higher inhibition potency from the initial screening. IC50 values ranged from 1.9 to 24 µM. In addition, the concentration of these compound in aqueous solution with artificial membranes containing human OCT3 protein was measured. The concentration of compound 6 (SR-2045) was significantly reduced in the presence of human OCT3. Therefore, these compounds have the potential to be further developed as novel antidepressant and human OCT3 detection agent. Future investigations are needed to study the pharmacokinetic and pharmacological properties of these compounds and potential interaction with other transporters.